A biflagellate spermatozoon in the African bonytongue Heterotis niloticus (Teleostei, Osteoglossidae). Issue 2 (20th February 2019) - Mattei, Xavier; Marchand, Bernard; Quilichini, Yann
Abstract : In this transmission electron microscopy study, we describe the ultrastructure of the spermatozoon of Heterotis niloticus (Osteoglossiformes), which is distinguished by having two flagella. Our investigation also highlights the great diversity of sperm cell structures observed across osteoglossiform families, such as aflagellate (Gymnarchidae, Mormyridae), monoflagellate (Notopteridae, Pantodontidae) and biflagellate spermatozoa. As biflagellate spermatozoa are rare in vertebrates, we also summarize the orders and families known to possess this ultrastructural character, most of which are fishes.